Changes in microstructure and mechanical properties of P91 weld metal during creep - Zhang, Yan (2009)
Creep failure of the weld structure in P91 steel components in high temperature power plant applications is often a key factor limiting the lifetime of the components. Whilst creep failure in weld heat-affected zone (HAZ) regions has been studied widely, the creep properties of the weld metal itself have been less well documented. In this work, the creep response of P91 weld metal in isolation was investigated in terms of microstructural evolution and mechanical properties.